2020
DOI: 10.1111/twec.13010
|View full text |Cite
|
Sign up to set email alerts
|

Financial intermediation, trade agreements and international trade*

Abstract: Using a gravity model on a data set of 69 developed and developing countries over the period 1986–2006, we show that the trade‐promoting role of financial intermediation in the exporting country is mitigated when this country faces low exporting costs, that is when there is a regional trade agreement (RTA) between this country and the importing one. We also establish that this mitigating effect is reduced in financially constrained sectors, for which the role of financial intermediation remains crucial. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 109 publications
(222 reference statements)
0
5
0
Order By: Relevance
“…The ability of incumbents to block the development of financial markets is limited by trade and financial openness, and the new opportunities created by openness, which may generate sufficient additional profits that outweigh the negative effects of increased competition. Moreover, previous studies of Kong et al. (2021); Rathnayaka Mudiyanselage et al .…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 98%
See 2 more Smart Citations
“…The ability of incumbents to block the development of financial markets is limited by trade and financial openness, and the new opportunities created by openness, which may generate sufficient additional profits that outweigh the negative effects of increased competition. Moreover, previous studies of Kong et al. (2021); Rathnayaka Mudiyanselage et al .…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 98%
“…Diversification opportunities are granted to bank lenders that sell in different markets with varying business cycles. Also, diversification of trade openness opportunities allows the bank to benefit from alternative markets in case of loss in a sector (Nguyen and Vaubourg, 2021). Recent studies have demonstrated that globally integrated industries are likely to diversify investment (Bandura, 2020;Bazih and Vanwalleghem, 2021;Dauda et al, 2021;Ghosh and Sinha, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…8 That database uses the above-mentioned taxonomy of PTAs between 195 countries for the period 1950-2017. 9 This NSF-Kellogg database has been used in other subsequent studies (Nguyen and Vaubourg, 2021;Díaz-Mora, García-López, and González-Díaz, 2022) For more details, see https://kellogg.nd.edu/nsf-kellogg-institute-data-base-economic-integration-agreements. 9…”
Section: -2010: Ptas Come To Cover Over 60% Of World Tradementioning
confidence: 99%
“…Therefore, after controlling for sector fixed effects and especially year×sector level fixed effects, tariffs have little explanatory power. In untabulated tests, I get country-pair trade agreements information fromNguyen and Vaubourg [2021] and add a dummy variable in the regression. The dummy variable equals one if there is a trade agreement between origin and destination country in year t and equals zero otherwise.…”
mentioning
confidence: 99%